How Motivation and Normative Commitment Drive Employee Performance: A Case Study of a Lifestyle and Home Improvement Retailer in Bandung - Ujang Wawan Sam Adinata Adinata; Iwan Sidharta; Djadjat Suswanto; Adang Adang (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2026)
To sustain effective performance, modern retail corporations must continuously prepare themselves to anticipate and adapt to rapid market changes. This study investigates how motivation and normative commitment influence employee performance within the dynamic retail environment. The research team employs a descriptive-verificative method using a survey approach to collect primary data from employees working at a prominent home improvement and lifestyle retail company in Bandung. The statistical analysis utilizes path analysis to measure the precise impact and relationships between the variables. The empirical results demonstrate that both motivation and normative commitment significantly and positively drive employee performance. The novelty of this study lies in its specific contextual evaluation of normative commitment combined with adaptive motivation within the fast-evolving lifestyle retail sector in an emerging Indonesian metropolitan area. Practically, these findings imply that retail managers must strategically design tailored motivational programs and foster a strong sense of moral obligation among staff to build a resilient, high-performing workforce capable of navigating organizational transformations.